The 12 worst tornadoes of all time - Lüsted, Marcia Amidon (All-time worst disasters., 2019)
Profiles history's twelve worst tornadoes, documenting their location, lives lost, and legacy. Each profile includes images and statistics, and select entries include critical thinking questions. Includes tips on how to stay safe during a tornado, a glossary, sources for further information, and an index.